Eksistensi Delik Konstitusional: Perspektif Hukum Pidana dan Hukum Tata Negara - Moh. Ali Hofi (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
A constitutional offense constitutes a violation of the fundamental norms enshrined in the constitution, committed by public officials or state institutions. Such violations are not only political in nature but also carry juridical dimensions closely related to criminal law. This article aims to examine the existence and urgency of regulating constitutional offenses from two main perspectives: constitutional law and criminal law. The research employs a normative juridical approach, emphasizing conceptual analysis and relevant legal regulations. This study also highlights the necessity of integrating constitutional mechanisms with criminal law enforcement to establish a system of accountability that is fair, proportional, and upholds the rule of law. Harmonizing these two areas of law is crucial to preserving the supremacy of the constitution in the practice of state governance.